Crush testing approach for flat-plate fibrous materials. (1st November 2020) - Lausch, J.; Takla, M.; Schweiger, H.-G.
Abstract: A novel crush testing approach is presented to obtain crush properties of flat-plate fibrous materials. To validate the proposed approach, fully constrained specimens of different materials were crushed. The inevitable component, the splitting force, included in the measured force, emanating from shearing, tearing, and friction at specimen edges, is isolated and deducted, resulting in the crushing force . An approximately linear relationship between the energy associated with the measured force and the specimen width was observed, suggesting width independent splitting energy. Consistent specific energy absorption (SEA) properties of fully supported flat-plate specimens were obtained using the proposed approach.